2002
DOI: 10.1046/j.1524-475x.2002.10605.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified tetracycline (CMT‐8) and estrogen promote wound healing in ovariectomized rats: Effects on matrix metalloproteinase‐2, membrane type 1 matrix metalloproteinase, and laminin‐5 γ2‐chain

Abstract: Estrogen deficiency is associated with impaired cutaneous wound healing. Remodeling of the extracellular matrix in wound healing involves the action of matrix metalloproteinases on basement membrane zone components, especially laminin-5. We studied the effects of estrogen and a potent matrix metalloproteinase inhibitor, chemically modified non-antimicrobial tetracycline, CMT-8, on wound healing in ovariectomized rats. At the tissue level, laminin-5 gamma2-chain expression was decreased and the migration-induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
2
36
0
3
Order By: Relevance
“…C, no injection at wound site; PBS, vehicle control. estrogen in maintaining a rapid rate of healing in both animal and human models, suggesting that the marked reduction of estrogen with age in both females and males plays a major role in age-related impaired woundhealing states (2)(3)(4)(5)(6)(7)(8). Moreover, evidence suggests that a crucial mechanism underlying the responses to estrogen involves a dampening of the inflammatory response, resulting in reduced proteolytic activity and enhanced matrix deposition (6).…”
Section: Discussionmentioning
confidence: 99%
“…C, no injection at wound site; PBS, vehicle control. estrogen in maintaining a rapid rate of healing in both animal and human models, suggesting that the marked reduction of estrogen with age in both females and males plays a major role in age-related impaired woundhealing states (2)(3)(4)(5)(6)(7)(8). Moreover, evidence suggests that a crucial mechanism underlying the responses to estrogen involves a dampening of the inflammatory response, resulting in reduced proteolytic activity and enhanced matrix deposition (6).…”
Section: Discussionmentioning
confidence: 99%
“…17␤-Estradiol 3-benzoate was demonstrated to be pro-proliferative in connective tissue (25) and in skin and lung fibroblasts (26) but to diminish cell proliferation in the renal ablation model (5). Estrogens normalized wound bed collagen contents and structure in the OVX rat model (27). In mesangial cell cultures, genistein, a selective estrogen receptor modulator (14), and 17␤-estradiol 3-benzoate reduced expression of collagen types I and IV (28).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline can also reduce inflammation by reducing synthesis of nitric oxide (NO) (101,102,115). Evaluation of a chemically tetracycline analogue in an animal study (116) also showed that local therapy reduced levels of MMP-8 and MMP-13 mRNA in dermal wounds of rats. Supporting this concept, an initial report (117) of a randomized controlled trial showed improved healing of chronic diabetic foot ulcers treated with a topical doxycycline gel.…”
Section: Local Therapy With Protease Inhibitorsmentioning
confidence: 99%